PENGARUH KARAKTERISTIK INDIVIDU, KOMITMEN ORGANISASI, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEGAWAI - Luh Made Ayu Windari Putri; Made Ika Prastyadewi; I Nyoman Resa Adhika (STMIK Pringsewu, 2023)
Performance is the level of effectiveness and efficiency shown by employees in carrying out their daily duties in an organization or company at a certain period. Improving employee performance is the most serious management challenge because the success of achieving goals and the survival of the organization depends on the quality of human resource performance in it. The more employees who have high performance, the effectiveness and efficiency of work in company activities will be maximized. This study aims to determine how the influence of individual characteristics, organizational commitment, occupational safety and health on employee performance at PT Tirta Investama Mambal. PT Tirta Investama Mambal is located in Br. Gumuasih, Mambal Kajanan, Abiansemal, Badung. The population in this study were 300 employees. Determination of the sample using the slovin method, with stratified proportionate random sampling technique, so that the sample used was 172 employees. Data analysis techniques using multiple linear regression analysis techniques. The results showed that individual characteristics had a positive and significant effect on employee performance at PT Tirta Investama Mambal, organizational commitment had a positive and significant effect on employee performance at PT Tirta Investama Mambal, occupational safety and health had a positive and significant effect on employee performance at PT Tirta Investama Mambal.